‘Quasi-Tricritical’ and Glassy Dielectric Properties of a Nematic Liquid Crystalline Material - Aleksandra Drozd-Rzoska (Crystals, 2020)
Results of dielectric studies in the nematic and isotropic liquid phases of pentylcyanobiphenyl (5CB), a model rod-like liquid crystalline material, are shown. They are based on the discussion of the evolution of dielectric constant ( <semantics> ε </semantics> ), its changes under the strong electric field (nonlinear dielectric effect, NDE), and finally, the primary relaxation time. It is shown that changes in <semantics> ε <mfenced> T </mfenced> </semantics> and NDE are entirely dominated by the impact of pretransitional fluctuations (pre-nematic and pre-isotropic, respectively) which are associated with the weakly discontinuous character of the isotropic–nematic phase transition. This influence also extends for the low-frequency, ionic species dominated, region. Notable, that the derivative-based and distortions sensitive analysis revealed the tricritical nature of the I-N transition. Although the glass transition in 5CB occurs in the deeply supercooled state at <semantics> T g ≈ − 68 <mtext> </mtext> ° C </semantics> , the dynamics (changes of the primary relaxation time) follow a previtreous pattern both in the isotropic and in the nematic phase. Finally, the discussion of the ’molecular’ vs. ‘quasi-critical’ characterizations of the isotropic and nematic phases is presented. It shows the evident prevalence of the ‘quasi-critical-picture’, which offers the consistent temperature parameterization in the total tested temperature range.